Braconid wasps of subfamily Alysiinae (Hymenoptera: Braconidae) as endoparasitoids of Selachops flavocinctus Wahlberg, 1844 (Diptera: Agromyzidae) in the Central Urals, Russia - Kostromina, Tatiana S.; Timokhov, Alexander V.; Belokobylskij, Sergey A. (Zootaxa, 2016)
The Agromyzidae fly Selachops flavocinctus Wahlberg, 1844 as host of the Alysiinae genera Asyntactus Marshall, 1898 (Alysiini) and Protochorebus Perepechaenko, 1997 (Dacnusini) is recorded for the first time. A new species from Central Urals, Protochorebus pervushini sp. nov., is described and illustrated. The new material for Asyntactus rhogaleus Marshall, 1898 is studied. A key to Protochorebus species is provided. Description of puparium of Selachops flavocinctus and new data on its life history are published for the first time.